Effects of exercise on circadian rhythms of cortisol - Erdemir, I.; Kizilet, A.; Bozdogan, T. K. (International Journal of Sports Science, 2013)
This study was to investigate the effects of exercise on the circadian rhythm of cortisol practiced at the lowest and peak levels of cortisol circadian rhythms in 10 males (age 20 years). Measurements were taken over a four-week period. In first week, physiological parameters, body mass index and performance parameters were measured and psychological tests conducted for all participants. In second week, circadian rhythm of cortisol was determined, and blood was taken every 4-hour over 24-hour (08:00am-12:00pm-16:00pm-20:00pm-00:00am-04:00am) from each participant. In third week, participants performed exercise day-morning at 08:00am at peak level of circadian rhythm of cortisol. Blood was taken before and after each exercise day-morning, as well as every four hours over 24-hour. Finally, in the last week of study, participants performed exercise day-evening at 20:00pm at the lowest point in circadian rhythm of cortisol and their blood were also taken before and after the exercises in addition to the four hour regimen. Exercising at the lowest and peak points of cortisol changed the body`s cortisol circadian rhythm. Cortisol levels were higher after exercise day-evening than after exercise day-morning. Although the level of cortisol at exercise day-evening was higher than at exercise day-morning, recovery period after exercise day-evening was faster than after exercise day-morning.